Bioengineered liposome–scaffold composites as therapeutic delivery systems. (June 2017) - Zylberberg, Claudia; Matosevic, Sandro
The therapeutic potential of liposomes can be amplified when combined with biomaterial scaffolds. Such configurations overcome the convergent demands of therapies by enabling enhanced delivery, environmental responsiveness and potency. Liposomes benefit from the increased physical and mechanical strength, favorable rheological properties and natural environment conducive to improved tissue formation that scaffolds provide, while enabling biocompatible delivery of hydrophilic and lipophilic compounds that can be further functionalized to achieve targeted delivery. Topical, ocular, oral, nasal and vaginal applications have been explored using various polymer- or nanofiber-based scaffolds. Mechanistic and rheological findings on complexation between biomaterials, liposomes and cargo have led to multimodal systems with tremendous clinical potential. A review of the key developments in bioengineered liposome–scaffold composites is presented in this manuscript.